2007
DOI: 10.1016/j.biopsych.2006.02.027
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium Regulates Glycogen Synthase Kinase-3β in Human Peripheral Blood Mononuclear Cells: Implication in the Treatment of Bipolar Disorder

Abstract: Background-Bipolar disorder has been linked to alterations in the multifunctional enzyme glycogen synthase kinase-3β (GSK3β). The mood stabilizer lithium inhibits GSK3β in vitro and in mouse brain, and this is currently the strongest known potential therapeutic target of lithium. We tested whether lithium modified GSK3β in vivo or in vitro in peripheral blood mononuclear cells (PBMCs) from healthy control and bipolar disorder subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 22 publications
3
91
0
5
Order By: Relevance
“…The observed reduced level of p-GSK3b, thus higher GSK3b activity in bipolar fibroblasts, may also underlie the rationale for lithium treatment of bipolar disorder since lithium directly inhibits GSK3b resulting in N-terminal phosphorylation of GSK3b at serine 9. 61 It was reported that the level of p-GSK3b in peripheral blood mononuclear cells from subjects with bipolar disorder under lithium treatment is significantly higher than that in healthy control subjects, 100 although no difference was detected between lithium-free bipolar and healthy controls. We postulate that the genetically heterogeneous nature of the samples may account for the failure of detecting p-GSK3b level difference between lithiumfree bipolar and healthy controls, as we encountered when including samples from members of non-Amish family 884 in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The observed reduced level of p-GSK3b, thus higher GSK3b activity in bipolar fibroblasts, may also underlie the rationale for lithium treatment of bipolar disorder since lithium directly inhibits GSK3b resulting in N-terminal phosphorylation of GSK3b at serine 9. 61 It was reported that the level of p-GSK3b in peripheral blood mononuclear cells from subjects with bipolar disorder under lithium treatment is significantly higher than that in healthy control subjects, 100 although no difference was detected between lithium-free bipolar and healthy controls. We postulate that the genetically heterogeneous nature of the samples may account for the failure of detecting p-GSK3b level difference between lithiumfree bipolar and healthy controls, as we encountered when including samples from members of non-Amish family 884 in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Akt activity was decreased by 31%, while GSK-3β activity was increased by 53% in patients with major depressive disorder (10 suicide and 10 non-suicide), compared with control subjects (10 suicide and 10 non-suicide); however, Akt and GSK-3α/ 3β protein levels were not changed between depressive patients and control subjects (54). In human peripheral blood mononuclear cells isolated from 23 healthy subjects, 9 bipolar disorder patients treated with lithium and 13 lithium-free bipolar disorder patients, Li et al (55) …”
Section: Depressive Patientsmentioning
confidence: 97%
“…However, at a therapeutic concentration of lithium, which is approximately 1 mM, GSK3 is only moderately inhibited because lithium's Ki for inhibition of GSK3 is approximately 2 mM. However, in addition to this direct inhibitory action of lithium on GSK3, treatment with lithium of mice, cultured cells, or human blood cells increases the inhibitory serine-phosphorylation of GSK3 [49,50;reviewed in Ref. 51].…”
Section: Psychiatric Diseases: Gsk3 and Mood Disordersmentioning
confidence: 99%
“…These are all difficult questions to address experimentally, so most evidence is based on correlative data. For example, lithium inhibits GSK3 both in mouse brain [49] and in human blood cells [50], which has led to the hypothesis that lithium also inhibits GSK3 in human brain. Since impaired serotonergic activity has long been linked to depression, the finding that enhanced serotonergic activity or anti-depressants acting on serotonergic systems cause inhibition of GSK3 in mouse brain in vivo lends further support to the possibility that impaired control of GSK3 is a component of mood disorders [54].…”
Section: Psychiatric Diseases: Gsk3 and Mood Disordersmentioning
confidence: 99%